ANALISA ORGANISASI PEMBELAJAR MENGGUNAKAN PENDEKATAN FIVE DISCPILINE - Nasution, Rosdiana Akmal (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2019)
School as an educational institution has an important role in developing the potential of students so that they will be able to carry out life's tasks as manuasia. Not only individually but also as part of the community. The progress of technology and information has made competition among schools increasingly increasing, not to mention the Sekolah Bogor Raya (SBR). This encourages SBR as a learning organization to carry out various innovations to be able to adapt to the environmental changes that occur. Such adaptability will only occur if the SBR management can develop its organization and facilitate learning from all its members. As part of a learning organization, teacher competence plays an important role as a learning agent. Learning organizations will not succeed if they do not accommodate their members to increase their potential. Knowledge, experience and creativity of teachers will be formed if they are given the opportunity to learn both individually and organizationally. Therefore this study aims to analyze the extent of the role of learning organizations in improving the competence of teachers.